GOOD CORPORATE GOVERNANCE, UKURAN PERUSAHAAN, DAN FINANCIAL LEVERAGE SEBAGAI PREDIKTOR PERATAAN LABA - Dewantari, Ni Putu Santi; Badera, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 10 No 2 (2015), 2015)
The purpose of this study was to determine the effect of good corporate governance, firm size, and financial leverage on income smoothing. This research was conducted on companies in Indonesia Stock Exchange that were included in the ranking CGPI (Corporate Governance Index Prediction) as the most trusted compan y in 2010-2012. Purposive sampling is used as a sampling method that produces a sample of 11 companies with a total of 33 observations during three years of research. Analysis using logistic regression with Eckel index as a measure of income smoothing. The results show that good corporate governance and firm size has no effect on the probability of income smoothing , while f inancial leverage has a negative and significant effect on the probability of income smoothing .
Keywords: Income Smoothing, Good Corporate Governance, Firm Size, Financial Leverage